(untitled) - Shurtleff, Malcolm C. (St. Paul, Minn, 1997)
This guide explains how to organize, equip, and operate a plant disease clinic. It offers precise details on how much space and what kind of equipment and supplies a clinic needs to handle specimens properly. Specific recommendations cover material and procedures needed to receive, store, examine, record, and report on specimens.
Keywords: Plant diseases; Diagnosis